Kinetic and cross-sectional studies on the genesis of hypoargininemia in severe pediatric plasmodium falciparum malaria - Florence, Salvatore M. (2019)
The low bioavailability of nitric oxide (NO) and its precursor, arginine, contributes to the microvascular pathophysiology of severe falciparum malaria. To better characterize the mechanisms underlying hypoargininemia in severe malaria, we measured the plasma concentrations of amino acids involved in de novo arginine synthesis in children with uncomplicated falciparum malaria (UM; n 61), children with cerebral falciparum malaria (CM; n 45), and healthy children (HC; n 109). We also administered primed infusions of L-arginine uniformly labeled with 13 C 6 and 15 N 4 to 8 children with severe falciparum malaria (SM; age range, 4 to 9 years) and 7 healthy children (HC; age range, 4 to 8 years) to measure the metabolic flux of arginine, hypothesizing that arginine flux is increased in SM. Using two different tandem mass spectrometric methods, we measured the isotopic enrichment of arginine in plasma obtained at 0, 60, 90, 120, 150, and 180 min during the infusion. The plasma concentrations of glutamine, glutamate, proline, ornithine, citrulline, and arginine were significantly lower in UM and CM than in HC (P 0.04 for all pairwise comparisons). Of these, glutamine concentrations were the most markedly decreased: median, 457 M (interquartile range [IQR], 400 to 508 M) in HC, 300 M (IQR, 256 to 365 M) in UM, and 257 M (IQR, 195 to 320 M) in CM. Arginine flux during steady state was not significantly different in SM than in HC by the respective mass spectrometric methods: 93.2 mol/h/kg of body weight (IQR, 84.4 to 129.3 mol/h/ kg) versus 88.0 mol/h/kg (IQR, 73.0 to 102.2 mol/h/kg) (P 0.247) by the two mass spectrometric methods in SM and 93.7 mol/h/kg (IQR, 79.1 to 117.8 mol/h/ kg) versus 81.0 mol/h/kg (IQR, 75.9 to 88.6 mol/h/kg) (P 0.165) by the two mass spectrometric methods in HC. A limited supply of amino acid precursors for arginine synthesis likely contributes to the hypoargininemia and NO insufficiency in falciparum malaria in children.